The effect of antihypertensive treatment on headache and blood pressure variability in randomized controlled trials: a systematic review. - Webb, A; Rothwell, P (2012)
Antihypertensive drugs reduce headache but it is unclear whether there are differences between drug classes. Calcium channel blockers (CCBs) decrease variability in systolic blood pressure (SBPV) and stroke risk more than other classes, possibly due to decreased vascular tone. If so, there might be a correlation between drug-class effects on variability in SBP and on headache. We determined antihypertensive class effects on SBPV and headache during follow-up in a systematic review of randomized controlled trials. We determined pooled estimates of treatment effect on group variability in BP (variance ratio, VR) and on the odds ratio for headache (OR) by random-effects meta-analysis. Antihypertensive drugs reduced the incidence of headache compared to placebo (OR = 0.75, 95% CI 0.69-0.82, p < 0.0001, 198 comparisons, 43,672 patients), but there was significant heterogeneity between drug classes (p = 0.0007) with a greater effect of beta-blockers compared to placebo (VR = 0.49, 0.33-0.68, p < 0.0001, 16 trials) or all other drug classes (OR = 0.73, 0.62-0.85, p = 0.0002, 49 trials) and a lack of effectiveness of CCBs (vs. placebo-OR = 0.95, 0.79-1.15, 65 trials; vs. other drugs-OR = 1.19, 1.05-1.35, p = 0.009, 101 trials). Drug-class effects on headache were opposite to effects on variability in SBP (vs. other drugs: CCB-VR = 0.81, 0.71-0.85, p < 0.0001; beta-blocker VR = 1.17, 1.07-1.28, p < 0.0001), but were unrelated to differences in mean SBP. Antihypertensive drugs reduce headache but the effect differs between classes, corresponding to their effects on SBPV and the risk of stroke. This may partly be explained by consistent antihypertensive class effects on vascular tone in the peripheral (variability) and cerebrovascular circulations (headache).